Seasonal variation of the nutritive value of fourwing saltbush (Atriplex canescens) - Medjekal S.; Bousseboua H. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The objective of this study was to evaluate the effect of season (winter, spring and summer) on the nutritive value of Atriplex canescens. The foliage of this shrub species was shade dried and analyzed for chemical composition. Gas and methane production were determined at 24 h incubation time. Season of sampling affected (P<0.05) the chemical composition, gas production, methane production, metabolizable energy and in vitro dry matter digestibility. The CP content was lower (P<0.05) in spring (168 g/kg DM) and summer (171 g/kg DM) versus winter (201 g/kg DM). In winter and spring, Atriplex canescens had higher (P<0.05) NDF, ADF, ADL contents than in summer. In all seasons, condensed tannins and EE content were generally low, whereas the ash content was extremely high (P<0.05) with (243.8 g/kg DM) in spring and (197.3 g/kg DM) in winter. The gas and methane production at 24 h incubation ranged from 47 to 67.66 ml and 4.67 to 8.70 ml respectively and decreased (P<0.05) in spring season. It is concluded that season had a significant effect on the nutritive value of Atriplex canescens; which is low in spring and relatively high in summer and winter.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)